Oxidation Stability Comparison between Zinc Dialkyldithiophosphate and Zinc Diamyldithiocarbarmate Induced Palm Oil Bio-lubricants / Muhamad Azwar Azhari ...[et al.] - Azhari, Muhamad Azwar; Md Sallehan, Muhammad Syafi; Nazri, Muhammad Naqib (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The environmental impact imposed by mineral based lubricant and the threat of petroleum depletion has triggered this study to search for an alternative lubricant using commercialized palm oil. The low oxidation stability of vegetable oil limits the performance of palm oil as a lubricant. This study introduces Zinc Dialkyldithiophosphate (ZDDP) and Zinc Diamlydithiocarbamate (ZDDC) into commercialized palm oil at different concentrations to investigate the effect of oxidation stability using a Rotating Pressure Vessel Oxidation Test. This study discovered that ZDDP displayed a better performance compared to ZDDC in terms of oxidation stability where it exhibited a longer oxidation time of 128 minutes at a concentration of 2 wt%. It can be concluded that the addition of organo zinc compound had improved the oxidation stability of commercialized palm oil as lubricant.